Experimental Investigation on Thermal Performance of Oscillating Heat Pipe with Water/Methanol Mixture as Working Fluids - Xu Tianxiao; Cui Xiaoyu; Li Zhihua; Sun Shende (Zhileng xuebao)
An experimental investigation was performed on the oscillating characteristics and thermal resistances of the oscillating heat pipe(OHP) with water/methanol mixture under varied mixing ratios(i.e. 13:1,4:1,1:1,1:4 and 1:13) and filling ratios (i.e. 90%,70%,62% and 55%) , which is compared with the pure working medium, water and methanol. Experimental results showed that the amplitude of the OHP with mixture was larger than the pure working fluid. Generally, the thermal resistance of the OHP with the mixture working medium was mostly higher than that with pure one when the filling ratio was more than 62%.The OHP with mixture was easier to dry out than that with pure one. When the filling ratios were 55%, the thermal resistance of the OHP with mixture rises faster. Specially, the working medium with little methanol (13:1) and much water was ideal because of the high heating power when dry out in 55% filling ratio. The thermal resistance of the OHP was mainly determined by the viscosity of working medium, phase equilibrium and so on. The primary factor changes in different working conditions.